3x+33=11x-66

Simple and best practice solution for 3x+33=11x-66 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+33=11x-66 equation:


Simplifying
3x + 33 = 11x + -66

Reorder the terms:
33 + 3x = 11x + -66

Reorder the terms:
33 + 3x = -66 + 11x

Solving
33 + 3x = -66 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
33 + 3x + -11x = -66 + 11x + -11x

Combine like terms: 3x + -11x = -8x
33 + -8x = -66 + 11x + -11x

Combine like terms: 11x + -11x = 0
33 + -8x = -66 + 0
33 + -8x = -66

Add '-33' to each side of the equation.
33 + -33 + -8x = -66 + -33

Combine like terms: 33 + -33 = 0
0 + -8x = -66 + -33
-8x = -66 + -33

Combine like terms: -66 + -33 = -99
-8x = -99

Divide each side by '-8'.
x = 12.375

Simplifying
x = 12.375

See similar equations:

| 1/5t-3=17 | | 9y-9y= | | 0=3t^2-16t+15 | | 0=3t^2+16t+15 | | c=(pi)10 | | y+6(-3)=9 | | -5n-1=-17+3 | | 8(b+3)=4b | | (5x+6)(2x-7)= | | y=20/3x-1 | | 1.5x-8.4=0.4+2.6x | | 3x(87*2)=0 | | 4x^2-19x+18=-6x+8 | | 20x-3y=1 | | x^2-x-16=-5x-4 | | 17x-13=-4x+47+15x | | 18x+125=12x+200 | | 18x=12x | | x+3x+15=0 | | 2cos^2=1+2sin^2x | | p=k-3/2k+5 | | 1000000=-40900x+1400000 | | 11=8-3x | | x^4-18x^2-16x-15=0 | | ln(5x-7)=6 | | (x-2c)(2x+c)+cx= | | 2y/5=12 | | 6c+2A=38 | | A=1/2(4)(4) | | 72/18 | | A=1/2(4/5)(4/5) | | A=1/2(16)(12) |

Equations solver categories